Immunomodulatory effect of dimethyloxallyl glycine/nanosilicates-loaded fibrous structure on periodontal bone remodeling - Zi-Qi Liu; Ling-Ling Shang; Shao-Hua Ge (Elsevier, 2021)
Background/purpose: Relieving immuno-inflammatory responses is the prerequisite step for treating periodontitis. The angiogenic small molecule, dimethyloxalylglycine (DMOG), and osteoinductive inorganic nanomaterial, nanosilicate (nSi) have a powerful effect on bone regeneration, whereas the roles in osteoimmunomodulation have not been totally uncovered. Our study aimed to explore the immunomodulatory effect of DMOG/nSi-loaded fibrous membranes on periodontal bone remodeling. Materials and methods: The fibrous membranes were prepared by incorporating DMOG and nSi into poly (lactic-co-glycolic acid) (PLGA) with electrospinning. The morphology features, surface chemical property and biocompatibility of DMOG/nSi-PLGA fibrous membranes were characterized. Thereafter, the fibrous membranes were implanted into rat periodontal defects, bone remodeling potential and immunomodulatory effect were evaluated by micro-computed tomography (micro-CT), histological evaluation and immunohistochemical analysis. Results: DMOG/nSi-PLGA membranes possessed favorable physicochemical properties and biocompatibility. After the fibrous membranes implanted into periodontal defects, DMOG/nSi-PLGA membranes could relieve immuno-inflammatory responses of the defects (reduction of inflammatory cell infiltration, CD40L and CD11b-positive cells), increased CD206-positive M2 macrophages, and eventually facilitated periodontal bone regeneration. Conclusion: DMOG/nSi-PLGA fibrous membranes exert protective effects during periodontal bone defect repairing, and steer immune response towards bone regeneration. Consequently, DMOG/nSi-PLGA fibrous membranes may serve as a promising scaffold in periodontal tissue engineering.